Perceived segmentation of center from surround by only illusory contours causes chromatic lateral inhibition - Elliott, Sarah L. (2013)
When a light and also its surrounding context slowly oscillate in chromaticity over time, the color appearance of the light depends on the relative phase of center and surround. The influence of the surround is generally accounted for by retinotopic center-surround organization with the surround inhibiting signals from the center. The traditional neural account, however, cannot rule out lateral inhibition due to cortical mechanisms sensitive to object segmentation cues. Experiments here reveal that illusory contours are sufficient to separate a center from its surround. Observers adjusted the Michelson contrast of a matching disk to equal the perceived modulation depth of a central area within a surround. Both the central test and matching disk were maintained at constant luminance and modulated in-phase at 2 Hz along one chromatic axis (L/(L+M) or S/(L+M)). The center was perceptually segmented from the surround by either a physical (retinotopic separation) or illusory (cortically represented) triangle contour. Segmentation of center from surround by the illusory contour strongly attenuated the perceived modulation depth for both chromatic axes. Further, the strength of attenuation was consistently greater with the illusory than the physically segmenting triangle. This cannot be accounted for by retinal center-surround antagonism; instead it points to a cortical neural representation of contours, with lateral inhibition following neural mechanisms sensitive to object segmentation cues.